Energy Management of Heavy-Duty Fuel Cell Electric Vehicles: Model Predictive Control for Fuel Consumption and Lifetime Optimization. Issue 2 (2020) - Ferrara, Alessandro; Okoli, Michael; Jakubek, Stefan; Hametner, Christoph
Abstract: This paper investigates the application of a simple but effective model predictive control concept for the fuel consumption and system lifetime optimization of a heavy-duty fuel cell electric vehicle. Energy management strategies primarily help extend the fuel cell lifetime by limiting shutdowns, transients and high-power operations to avoid detrimental conditions. In this framework, the proposed online control scheme determines a significant reduction of the average fuel cell power change rate and a small fuel consumption increment with respect to the control law that minimizes the fuel consumption, computed offline through the Pontryagin's minimum principle. These results refer to the real-world driving mission of a road freight vehicle, including the elevation gradient of the road, which highly affects the load request in downhill and uphill sections. However, this preliminary study does not include a speed prediction model, but it assumes that the speed is known without uncertainties over a relatively short time horizon.